2014
DOI: 10.1177/0300060514540631
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of the cadherin 13 gene in serum and its relationship with clinicopathological features of prostate cancer

Abstract: Objective: To investigate the clinical significance of cadherin 13 (CDH13) gene promoter methylation in the serum of patients with prostate cancer. Methods: This prospective study examined the methylation status of CDH13 in serum samples obtained from patients with primary prostate cancer and age-matched control subjects, using methylation-specific polymerase chain reaction. Associations between methylation status of CDH13 and various clinicopathological features and patient survival were evaluated. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
(47 reference statements)
1
18
0
1
Order By: Relevance
“…It has been shown that protocadherins behave as tumor suppressor genes in many solid cancers such as non-small-cell lung cancer, gastric and prostate cancer. It has also been demonstrated that their involvement is due to aberrant DNA methylation that determines an altered expression pattern [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that protocadherins behave as tumor suppressor genes in many solid cancers such as non-small-cell lung cancer, gastric and prostate cancer. It has also been demonstrated that their involvement is due to aberrant DNA methylation that determines an altered expression pattern [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individually, serum PCDH17 me , PCDC10 me and PCDH8 me were also associated with advanced clinical stage, higher preoperative serum PSA, as well as lymph node metastasis and shorter biochemical recurrence-free survival [193][194][195]. Besides being also associated with Gleason score, advanced tumor stage and high PSA, CDH13 me was further associated with shorter OS [183].…”
Section: Prognosis Predicition and Monitoringmentioning
confidence: 91%
“…DNA was extracted from 0.8 ml archived serum from each patient using the QIAmp DNA Blood Mini Kit (Qiagen, Valencia, CA, USA), according to the manufacturer’s instructions. The isolated DNA was modified with bisulfite using the EpiTect Bisulfite Kit (Qiagen, Valencia, CA, USA) and standard protocol as described previously [ 27 , 28 ]. The methylation status of PCDH10 was detected using MSP, as previously described [ 24 , 28 ].…”
Section: Methodsmentioning
confidence: 99%